Dissimilatory sulfate reduction in the cake layer of a full-scale anaerobic dynamic membrane bioreactor for hotel laundry wastewater treatment: Bacterial community and functional genes. (May 2022) - Zhou, Lijie; Ou, Pingxiang; Shao, Zhiyuan; Shen, Yichang; Lu, Jiahao; Zhuang, Wei-Qin
Graphical abstract: Highlights: DSR in cake layer of dynamic MBR treating hotel laundry wastewater was studied. DSR predominated over ASR during dynamic cake layer formation. Sulfate reduction through DSR was mainly depended on co-work between DSR bacteria. Transformation from SO3 2- to S 2- was the key role of DSR in cake layer formation. Abstract: Dissimilatory sulfate reduction (DSR) in cake layer of full-scale anaerobic dynamic membrane bioreactor for treating hotel laundry wastewater was studied. Change (Δ) of sulfate concentration (ΔSO4 2- ) was positively correlated to dynamic cake layer (DCL) development, while ΔS 2- was negatively correlated. ΔSO3 2- and ΔSorganic sulfur remained around 1.5–2.5 and 1.2–2.3 mg-S/L, respectively. Thus, DSR was the predominant sulfate reduction process in DCL. 33 binned genomes from DCL microbiome samples possessed one or more DSR functional genes. But only four binned genomes possess all functional genes, and thus can achieve complete DSR. However, no significant variations of these DSR bacteria was obseared during DCL development. Metagenomic analysis predicted that sulfate reduction in DCL was mainly carried out by collaborations between bacteria with incomplete DSR pathways. Among which, sulfite → sulfide by dissimilatory-sulfite-reductase expression bacteria was the key process. Overall results suggested that controlling dissimilatory-sulfite-reductase activities could prevent sulfide buildup in the effluent.